2016
DOI: 10.1002/cam4.669
|View full text |Cite
|
Sign up to set email alerts
|

AKT1 and BRAF mutations in pediatric aggressive fibromatosis

Abstract: Aside from the CTNNB1 and adenomatous polyposis coli (APC) mutations, the genetic profile of pediatric aggressive fibromatosis (AF) has remained poorly characterized. The aim of this study was to shed more light on the mutational spectrum of pediatric AF, comparing it with its adult counterpart, with a view to identifying biomarkers for use as prognostic factors or new potential therapeutic targets. CTNNB1,APC,AKT1,BRAF TP53, and RET Sanger sequencing and next‐generation sequencing (NGS) with the 50‐gene Ion A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
0
24
2
Order By: Relevance
“…Based on our previous results analyzing mesenteric DTF 20 , we first examined the mutational CTNNB1 status in correlation with clinicopathological features. Previous studies reported genomic CTNNB1 alterations in 67-92% of sporadic DTF cases demonstrated by conventional Sanger sequencing and limited to CTNNB1 exon 3 [7][8][9][19][20][21] (summarized in Table 3). In our present study, we conducted NGS with an increased sensitivity (≥10% allelic frequency) and detected deleterious CTNNB1 mutations in an enlarged fraction of n = 181/204 (89%) DTF cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous results analyzing mesenteric DTF 20 , we first examined the mutational CTNNB1 status in correlation with clinicopathological features. Previous studies reported genomic CTNNB1 alterations in 67-92% of sporadic DTF cases demonstrated by conventional Sanger sequencing and limited to CTNNB1 exon 3 [7][8][9][19][20][21] (summarized in Table 3). In our present study, we conducted NGS with an increased sensitivity (≥10% allelic frequency) and detected deleterious CTNNB1 mutations in an enlarged fraction of n = 181/204 (89%) DTF cases.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of genetic studies published so far applied conventional Sanger sequencing of CTNNB1 (limited to exon 3), focusing predominantly on the mutational subtype of sporadic DTF. Recently, Meazza et al analyzed a small cohort of DTF employing NGS for mutational analysis and reported potential clinical implications for pediatric (patients age ≤18 years) DTF harboring gain-of-function mutations in AKT1 and BRAF 19 . These findings suggest a more complex mutational spectrum of DTF than expected so far, which may potentially be associated with therapeutic implications.…”
mentioning
confidence: 99%
“…Genomic DNA was extracted from FFPE tumor sections with the GeneRead DNA FFPE kit (Qiagen, Hilden, Germany) and its quantity/quality was assessed by bioanalyzer. Mutational data were obtained by targeted next‐generation sequencing (T‐NGS) using the Ion AmpliSeq Cancer Hotspot Panel v2 (Life Technologies, Carlsbad, CA, USA) with the Ion‐Torrent Personal Genome Machine platform (Life Technologies) . Library preparation, emulsion polymerase chain reaction (PCR) and chip loading were performed as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…Library preparation, emulsion polymerase chain reaction (PCR) and chip loading were performed as previously described . Data were processed by using Torrent Suite and variants were analyzed as previously described . We looked at molecular alterations, which could potentially pave the way for targeted therapeutic approaches, and we leveraged on the alterations already reported in salivary gland cancer and basal cell carcinoma whose histological profiles could resemble the ones of SAC.…”
Section: Methodsmentioning
confidence: 99%
“…The libraries were prepared by IonAmpliSeq Library kit 2.0 (Thermo Fisher). 16 Emulsion polymerase chain reaction and chip loading were performed on the IonChef System (Thermo Fisher), according to the manufacturer's instructions. Sequencing was performed on the ION S5 XL System (Thermo Fisher) using Ion 540 Chips and Ion 540 Kit-Chef according to the manufacturer's instructions (MAN0010846).…”
Section: Molecular Analysesmentioning
confidence: 99%